Public Deliberation in Russia: Deliberative Quality, Rationality and Interactivity of the Online Media Discussions - Filatova, Olga (2019)
Deliberation research is now undergoing two emerging trends: deliberation is shifting from offline to online, as well as from an inherently democratic concept to the one applicable to less competitive regimes (He & Warren, 2011). The goal of this article is to study the peculiarities of deliberative practices in hybrid regimes, taking online discourse on the Russian anti-sanctions policy as a case. We use the Habermasian concept of basic validity claims to assess deliberation quality through the lens of argumentation and interactivity. Our findings suggest that deliberative practices can exist in non-competitive contexts and non-institutionalized digital spaces, in the form of intersubjective solidarities resulting from the everyday political talk among ordinary citizens. Such deliberations can be counted as argumentative discourses, although in a special, casual way—unlike the procedural rule-based debates. Generally, as in established liberal democracies, deliberation in Russia tends to attract like-minded participants. While the argumentative quality does not seem to vary across the discussion threads sample, the level of deliberative interactivity is higher on pro-government media, accompanied with the higher level of incivility. On the other hand, discourses on independent media are distinctively against the government policy of food destruction. The democratic value of such deliberations is unclear and might depend on the political allegiance and ownership of the media. Though some discourses can be considered democratic, their impact on decision-making remains minimal, which is a key constraint of deliberation.